Assessment of biodegradation kinetics and mass transfer aspects in attached growth bioreactor for effective treatment of brilliant green dye from wastewater - Tripathi P.; Tiwari S.; Sonwani R.K.; Singh R.S. (My University, 2025)
In this study, Bacillus licheniformis immobilized with low-density polyethylene (LDPE) was employed to degrade Brilliant Green (BG) dye from wastewater in a packed bed bioreactor (PBBR). Bacterial growth and extracellular polymeric substance (EPS) secretion were also assessed under different concentrations of BG dye. The impacts of external mass transfer resistance on BG biodegradation were also evaluated at different flow rates (0.3–1.2 L/h). A new mass transfer correlation JD=5.71NRe-0.3 was proposed to study the mass transfer aspects in attached-growth bioreactor. The intermediates, namely 3- dimethylamino phenol, benzoic acid, 1–4 benzenediol, and acetaldehyde were identified during the biodegradation of BG and, subsequently degradation pathway was proposed. Han - Levenspiel kinetics parameters μmax and Ks were found to be 0.185 per day and 115 mg/L, respectively. The new insight into mass transfer and kinetics support the design of efficiently attached growth bioreactor to treat a wide range of pollutants. © 2023 Elsevier Ltd